Divine Agency and the Principle of the Conservation of Energy - Larmer, Robert A. H. (Zygon, 2009)
Abstract. Many contemporary thinkers seeking to integrate theistic belief and scientific thought reject what they regard as two extremes. They disavow deism in which God is understood simply to uphold the existence of the physical universe, and they exclude any view of divine influence that suggests the performance of physical work through an immaterial cause. Deism is viewed as theologically inadequate, and acceptance of direct immaterial causation of physical events is viewed as scientifically illegitimate. This desire to avoid both deism and any positing of God as directly intervening in the physical order has led to models of divine agency that seek to defend the reality of divine causal power yet affirm the causal closure of the physical. I argue, negatively, that such models are unsuccessful in their attempts to affirm both the reality of divine causal power acting in the created world and the causal closure of the physical and, positively, that the assumption that underlies these models, namely that any genuine integration of theistic and scientific belief must posit the causal closure of the physical on pain of violating well-established conservation principles, is mistaken.